2000
DOI: 10.1093/ps/79.12.1767
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enzyme addition to broiler diets containing high concentrations of canola or sunflower meal

Abstract: The effects of two commercial enzyme products on the nutritive value of canola meal (CM) and sunflower meal (SFM) were determined in a classical AME bioassay with special emphasis on the utilization of nonstarch polysaccharides (NSP). The enzymes were added to semi-purified broiler grower diets based on corn and casein containing 35% CM or 35% SFM, respectively. Feed intake, growth, and AME of the diets were significantly (P < 0.001) affected by type of oilseed meal included in the diet. Birds fed the SFM-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
78
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 22 publications
11
78
1
4
Order By: Relevance
“…Tavernari et al obtained better dry matter digestibility and better coefficients of Ca and P metabolizability in broilers fed diets with SFM supplemented with enzymes. Kocher et al (2000), on the other hand, did not observe any effects of enzyme addition in feeds containing sunflower meal.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Tavernari et al obtained better dry matter digestibility and better coefficients of Ca and P metabolizability in broilers fed diets with SFM supplemented with enzymes. Kocher et al (2000), on the other hand, did not observe any effects of enzyme addition in feeds containing sunflower meal.…”
Section: Introductionmentioning
confidence: 64%
“…Exogenous enzymes are frequently added to feeds to improve the nutritional value of feedstuffs, particularly of those containing high fiber levels (Kocher et al, 2000). Tavernari et al obtained better dry matter digestibility and better coefficients of Ca and P metabolizability in broilers fed diets with SFM supplemented with enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The BW of broilers fed a diet supplemented with 7 and 10% CM decreased by 8.9 and 13.2%, respectively (Borcea et al, 1996). In contrast, it has been reported that the replacement of 100% SBM by CM maintained broiler performance, provided diets are supplemented with lysine (Leeson et al, 1987;Kocher et al, 2000). The observed discrepancy in CM feeding values prompted us to study the effects of the dietary inclusion of graded levels of CM on the growth performance of broilers.…”
Section: Introductionmentioning
confidence: 98%
“…Despite all these, several authors have showed no adverse effect of high dietary inclusion of CM on growth performance of broilers (Kocher et al, 2000;Baloch et al, 2003). CM can be included effectively in the diet of broilers at a level of up to 30% without affecting growth performance, as long as diets are formulated on the basis of digestible amino acid (Canola Council of Canada, 2009).…”
Section: Introductionmentioning
confidence: 99%